1995
DOI: 10.1016/0168-1176(95)04248-j
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of H3+ and D3+ ions in a flowing afterglow plasma

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 49 publications
5
71
1
Order By: Relevance
“…The second study, performed after a modification of their flow tube, resulted in a factor-of-two lower value of 7.8 × 10 -8 cm 3 /s at 300 K. Laube et al [17] did not find any variation of the apparent recombination as a function of afterglow time. In contrast, Gougousi et al [16] saw a decline of the recombination rate at late times and found that the apparent recombination rate (inferred from the early afterglow decay) increased from 1. . Gougousi et al attempted to explain their data in terms of a mixture of two different H 3 + vibrational states, but eventually preferred the explanation that the H 3 + recombination proceeded by a three-body mechanism in which both electrons and neutral hydrogen play a role.…”
Section: Afterglow Data After 1984mentioning
confidence: 95%
“…The second study, performed after a modification of their flow tube, resulted in a factor-of-two lower value of 7.8 × 10 -8 cm 3 /s at 300 K. Laube et al [17] did not find any variation of the apparent recombination as a function of afterglow time. In contrast, Gougousi et al [16] saw a decline of the recombination rate at late times and found that the apparent recombination rate (inferred from the early afterglow decay) increased from 1. . Gougousi et al attempted to explain their data in terms of a mixture of two different H 3 + vibrational states, but eventually preferred the explanation that the H 3 + recombination proceeded by a three-body mechanism in which both electrons and neutral hydrogen play a role.…”
Section: Afterglow Data After 1984mentioning
confidence: 95%
“…In the afterglow experiments of Spanel and Smith [6] and of Gougousi et al [7] it was found that the recombination rate slowed down in the late afterglow when the electron density is low. This effect may be due to a ternary reaction with electrons but alternate explanation exist (vibrationally excited ions) that complicate matters.…”
Section: Experimental Data On Third-body Effectsmentioning
confidence: 99%
“…p-electrons, with 'penetrating orbits') interact more efficiently with the ion core and can induce rapid predissociation of the molecular core, thereby completing recombination. The effect of l-mixing due to electrons on H + 3 recombination was first considered by Gougousi et al [18]. Here, we focus on proposed models in which helium atoms are the l-mixing agent.…”
Section: (A) Collisional Radiative Recombination and Collisional Dissmentioning
confidence: 99%
“…Most available data indicate that the electron density (in the experimental range) has little effect. An element of doubt remains, however (see [18]). …”
Section: Afterglows In Rare-gas/h 2 Mixturesmentioning
confidence: 99%
See 1 more Smart Citation